Sistema de Informações Geográficas para o Mapeamento e Controle do Crime: Proposta para o Município de Feira de Santana, Bahia - Dos Santos, Josias Paulo [UNESP] (My University, 2005)
The mapping crime using a Geographical Information System (SIG), besides a scientific activity, is an intelligent strategy of violence figthing, constituted in a base of information for discerning analysis of data, for better understanding and control of criminal action. This proposal of a GIS, for the region of Feira de Santana, State of Bahia - Brazil, shows how the mapping crime can be carried through a set of computational tools composed of hardware and software, through space information, in the study of its causes, consequences and ways for its control.
Geographical information system for mapping and crime control: Proposal for the region of Feira de Santana, Bahia
Keywords: Crime Control; Feira de Santana; Geoprocessing; Geotechnologies; GIS; Mapping